Organization of Pedagogical Practice of Students in Khmelnytskyi Humanitarian-Pedagogical Academy: History and Modern Times - Mashkina, Liudmyla; Kazakova, Nataliia (Pedagogical Discourse, 2017)
The article describes the peculiarities of the organization of pedagogical practice in the Khmelnytskyi Humanitarian-Pedagogical Academy. The historical aspects of its development and modern tendencies of functioning are shown. The organizational and methodical principles of practice in the pedagogical school, the technical school, the pedagogical college, the college of the humanitarian pedagogical institute and the academy are determined. It is focused on the types and contents of pedagogical practice, bases, documentation. The attention was paid to the procedure of protection of practice, the activities of practice directors, teachers of general and preschool establishments, scientific developments on problems of practical training. In particular, collections of scientific works, dissertation researches, scientific and practical conferences on pedagogical practice. Pedagogical practice in Khmelnytskyi Humanitarian-Pedagogical Academy is one of the most effective, productive (professionally) directed form of student training. The role of pedagogical practice in the formation of the personality of the educator, teacher, teacher, manager and in the mastering of the pedagogical profession is extremely high. During practice, students have the opportunity to assert themselves in the new status-role position, identify themselves with the professional model of the future teacher, who performs various functions: educational, educational, developmental, maternal, diagnostic, socialization, etc.; to form their own individual style of professional activity with children, parents and colleagues; to form professional abilities; to define professional prospects for them and ways of their achievement, as well as to strive for constant improvement and creativity.